2013
DOI: 10.1037/a0030157
|View full text |Cite
|
Sign up to set email alerts
|

Examining the relationships between prenatal methamphetamine exposure, early adversity, and child neurobehavioral disinhibition.

Abstract: Methamphetamine use is a growing problem among pregnant women in the United States. Many negative consequences of methamphetamine use have been documented for the users, but little research has examined the long-term association between prenatal methamphetamine exposure (PME) and childhood outcomes. The current study examined the extent to which PME was predictive of childhood neurobehavioral disinhibition (ND), as well as the extent to which early adversity mediated this relationship. A sample of 320 mother–i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
28
0
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 78 publications
(140 reference statements)
3
28
0
1
Order By: Relevance
“…During infancy, the IDEAL study reported PME effects on poor fine motor performance, decreased arousal, and increased stress. 11 In 3–6.5 year-olds, PME was associated with executive function deficits 12 and behavior problems, including increased emotional reactivity, anxiousness, depressiveness, attention problems, withdrawn behavior, 13 and poor inhibitory control. 14 …”
Section: Introductionmentioning
confidence: 99%
“…During infancy, the IDEAL study reported PME effects on poor fine motor performance, decreased arousal, and increased stress. 11 In 3–6.5 year-olds, PME was associated with executive function deficits 12 and behavior problems, including increased emotional reactivity, anxiousness, depressiveness, attention problems, withdrawn behavior, 13 and poor inhibitory control. 14 …”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with previous work that demonstrated PME and early adversity were associated with behavioral and emotional control issues at age 5 years. [11]…”
Section: Discussionmentioning
confidence: 99%
“…putamen, globus pallidus, hippocampus, and caudate) with memory and attention deficits among children with PME from 3-16 years old[30]. In previous findings from the IDEAL study, Abar et al[11] examined the extent to which PME was predictive of childhood neurobehavioral disinhibition (ND) and the extent to which early adversity (birth through year 3) mediated this process. At age 6.5 years of age PME was associated with issues regarding behavioral and emotional control at 5 years of age, which was associated with executive function deficits at 6.5 years.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations